2021
DOI: 10.3390/cancers13030515
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of T Cell Factor 1 in Sustaining CD8+ T Lymphocyte-Directed Anti-Tumor Immunity

Abstract: T cell factor 1 (TCF1) is a transcription factor that has been highlighted to play a critical role in the promotion of T cell proliferation and maintenance of cell stemness in the embryonic and CD8+ T cell populations. The regulatory nature of TCF1 in CD8+ T cells is of great significance, especially within the context of T cell exhaustion, which is linked to the tumor and viral escape in pathological contexts. Indeed, inhibitory signals, such as programmed cell death 1 (PD-1) and cytotoxic-T-lymphocyte-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 109 publications
1
7
0
Order By: Relevance
“…To further explore the mechanism by which TCF1 regulates CLL prognosis and the partner molecules interacting with TCF1, functional and pathway enrichment analysis revealed that TCF1 is positively correlated with BCL11B, which is mainly involved in T cell differentiation and activation and immune regulation in CLL patients, in accordance with the literature (20,22). Moreover, BCL11B was highly consistent with TCF1 in terms of decreased expression and the prediction of poor prognosis based on analysis of public datasets and HNCH data.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…To further explore the mechanism by which TCF1 regulates CLL prognosis and the partner molecules interacting with TCF1, functional and pathway enrichment analysis revealed that TCF1 is positively correlated with BCL11B, which is mainly involved in T cell differentiation and activation and immune regulation in CLL patients, in accordance with the literature (20,22). Moreover, BCL11B was highly consistent with TCF1 in terms of decreased expression and the prediction of poor prognosis based on analysis of public datasets and HNCH data.…”
Section: Discussionsupporting
confidence: 74%
“…These findings indicated that BCL11B is highly correlated with TCF1 and coordinates with this gene to maintain the stem-like properties and cytotoxicity of effector CD8+ T cells (22,24,41). Unfortunately, we found that TCF1 and BCL11B expression was decreased in CLL patients, and this resulted in impaired differentiation potential for effector CD8+ T cells (21,22), which clinically manifested as the accumulation of terminally differentiated T cells (44), immune function dysfunction, and further rapid CLL progression. Although the data were not yet significant enough, this, to some extent, explains why decreased TCF1 and BCL11B expression leads to poor prognosis for patients with CLL.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…DNs subsequently express CD4 and CD8 upon the induction of the thymus microenvironment to become double-positive cells (DPs). 30 Then, DPs develop into single-positive T cells expressing the surface markers CD4 or CD8 through the action of a series of regulatory signals, such as protein arginine methyltransferase 5 31 and T cell factor 1 32 to coregulate the immune response. Therefore, T cells are often divided into CD4 + T cells or CD8 + T cells.…”
Section: Brief Primer On Immune Cell Biologymentioning
confidence: 99%